THE NAMES OF DOMESTIC ANIMALS IN MONUMENT AT-TUHFA AZ-ZAKIA FIL-LUGAT AL-TURKI (Journal of Oriental Studies, 2016)
The article discusses the the names of domestic animals, that had given in medieval monument "Kitab al-Tuhfat-uz-zakiyya fil-lugat-it-turkiyya" ("The precious gift of Turkic languages").
Keywords: manuscript; zoonyms; medieval monument; Kipchak language; dictionary